Konjungsi Subordinatif dalam Cerpen Kasur Tanah Karya Muna Masyari - Sariasih, Yanti; Humairo, Aisyah; Astuti, Cekly Panti; Puryanti, Yulia; ‘Ayun, Zahra Qurrota (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to describe the use of subordinating conjunctions in the short story Kasur Tanah by Muna Masyari. The method used in this study is a qualitative descriptive approach. The source of research data is the short story Kasur Tanah by Muna Masyari. The technique used to collect data is the read-note technique. The analysis technique used is descriptive technique. The results of this study show that the use of subordinating conjunctions contained in the short stories Kasur Tanah is quite diverse. The use of subordinating conjunctions in question includes time subordinating conjunctions, goal subordinating conjunctions, cause subordinating conjunctions, concessional subordinating conjunctions, method subordinating conjunctions, tool subordinating conjunctions, and comparative subordinating conjunctions. The results of this study can be used as a learning reference for all readers.